BRCA1 promoter deletions in young women with breast cancer and a strong family history: a population based study. - Smith, LD (2007)
Women diagnosed with breast cancer before the age of 40 years who have a strong family history of breast and/or ovarian cancer were selected from an Australian population-based case-control-family study for large deletion screening within the BRCA1 promoter. Deletions within the BRCA1 promoter region are usually not detected by the methods applied in routine clinical mutation detection strategies. Fifty-one of the 66 women (77%) who met our inclusion criteria were tested for promoter deletions using linkage disequilibrium analysis of two BRCA1 polymorphic sites (C/G1802 and Pro871Leu) and Multiplex Ligation-dependent Probe Amplification. Two cases of BRCA1 promoter deletion involving exons 1A-2, and exons 1A-23, were detected. The morphology of the breast cancers arising in these women with BRCA1 promoter deletions was consistent with the morphology associated with other germline BRCA1 mutations. Large genomic deletions that involve the promoter regions of BRCA1 make up 20% (2/10) of all known BRCA1 mutations in this group of young women with a strong family history of breast and ovarian cancer. Our data supports the inclusion of testing for large genomic alterations in the BRCA1 promoter region in routine clinical mutation detection within BRCA1.